Pink Ribbons, Inc. [videorecording (DVD)] - Pool, Léa, 1950-; King, Samantha, 1970-; Brenner, Barbara A.; Ehrenreich, Barbara; Brinker, Nancy; Love, Susan M.; Olopade, Olufunmilayo I. (First Run Features, 2012)
Pink ribbons are everywhere: T-shirts, hats, yogurt cups, KFC buckets, car ads, NFL stadiums - the list goes on and on. They make people feel good, as if engaged in a successful battle against breast cancer. But who is really benefitting? More and more women are diagnosed with breast cancer every year. Wouldn't it be something if some of the very companies that profit from their pink marketing campaigns have actually contributed to the epidemic by selling known carcinogens?